2017
DOI: 10.18639/merj.2017.03.403737
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Leadership Style, Organizational Culture, and Job Satisfaction in the U.S. Healthcare Industry

Abstract: The purpose of this quantitative, correlational study, based on the theoretical framework of transformational leadership, was to examine the relationships between leadership style, organizational culture, and job satisfaction in the U.S. healthcare industry. The study addressed a problem faced by U.S. healthcare leaders, who are currently unaware as to how transformational leadership and organizational culture can impact job satisfaction in an industry with high burnout and low satisfaction levels. The followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
(81 reference statements)
1
7
0
Order By: Relevance
“…A leader using a transformational leadership style acts as a role model, adds meaning and challenge to subordinates’ work, encourages subordinates to be creative and approach problems in new ways, pays attention to the individual subordinate’s needs and provides coaching and mentoring ( Skakon et al , 2010 ). Transformational leadership has been shown to have a positive impact on job satisfaction and well-being ( Sow et al , 2017 ; Morsiani et al , 2016 ; Sudha et al , 2016 ) as well as on the quality of care in the health sector ( Havig, 2011 ; Westerberg and Tafvelin, 2014 ).…”
Section: Perspectives On Leadershipmentioning
confidence: 99%
“…A leader using a transformational leadership style acts as a role model, adds meaning and challenge to subordinates’ work, encourages subordinates to be creative and approach problems in new ways, pays attention to the individual subordinate’s needs and provides coaching and mentoring ( Skakon et al , 2010 ). Transformational leadership has been shown to have a positive impact on job satisfaction and well-being ( Sow et al , 2017 ; Morsiani et al , 2016 ; Sudha et al , 2016 ) as well as on the quality of care in the health sector ( Havig, 2011 ; Westerberg and Tafvelin, 2014 ).…”
Section: Perspectives On Leadershipmentioning
confidence: 99%
“…For organisations, especially tertiary hospitals, it would be interesting to analyse if the steady changes in transformational leadership can impact the organisational culture. 56 If the improvement in transformational leadership steadily changes the organisational culture, it could be possible that it has a positive impact on role behaviour, such as in-role and extra-role behaviors 57 that would help hospitals in dealing with the growing pressure. However, so far research on the mechanisms that explain the long-term stability of the change in leading behaviour is lacking and should be addressed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the positive relationship between work engagement, quality of service, customer loyalty and profitability [26,31,32]. Recent studies have linked the positive relationship between organizational culture and work engagement [23,[33][34][35]. More specifically, according to Katz Navon, et al [36], it was found that beurocratic culture and production culture had a significant impact on employees' work engagement level, as long to patients' services received.…”
Section: • Organizational Culture and Work Engagementmentioning
confidence: 99%